ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Gervaise, David; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of leverage, firm size, net working capital and profitability on cash holding in manufacturing companies in 2018-2020. The research sample was selected based on the purposive sampling method and the selected sample was 72 companies. The data processing technique used in this study uses multiple regression analysis assisted by the EViews 12 software and Microsoft Excel 2019. The results show that leverage has no significant negative effect on cash holding. Firm size has no significant positive effect on cash holding, while net working capital and profitability have a significant positive effect on cash holding.